Analysis of Digital Marketing Literacy, Product Legality On Purchasing Decisions With Consumer Protection As Mediation For Smes In Labuhanbatu - Zelibu, Yanto (LPPM Universitas Labuhanbatu, 2024)
This research aims to analyze the relationship between digital marketing literacy, product legality on purchasing decisions and connect the mediating role of consumer protection. This research is a quantitative descriptive research, the population in this research is all visitors to the Gelugur Labuhanbatu Market, while the sample used is specifically consumers at the Gelugur Labuhanbatu Market, totaling 150 respondents. Data collection was carried out by distributing questionnaires and direct interviews. Data analysis used in this research uses Structural Eqation Model (SEM) with the help of the SmartPLS application. The results of this research show that digital marketing literacy has a positive and significant effect on purchasing decisions. Furthermore, product legality was also found to have a positive and significant influence on purchasing decisions. Finally, this research found that consumer protection was able to mediate the relationship between digital marketing and purchasing decisions and consumer protection was also able to mediate the relationship between product legality and purchasing decisions. This means that consumers who understand consumer protection will predominantly consider the type of marketing used and consider the legality of the product before making a purchase.